Dramaturgy of Sila Dance Hari Ghulur - Ahmad Faishal (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2021)
This article is a study of Sila Dance by Hari Ghulur using Dramaturgyapproach, namely Socio Dramatic aspect. The theory used in thisarticle is semiotics theory of Roland Barthes with descriptiveinterpretative method. Sila dance showis understood as art and culturaldocument that represent the cultural identity of a society, namelyMadurese society. Madurese context is the basis for this researchbecause Hari Ghulur comes from Madura. In this case, there is a closecultural context between the choreographer, dancer, researcher and thetext of Sila show. The result of the analysis in this study isatdenotative meaning level describing dancer identity who is tough andstrong, while at connotative meaning level it represents Maduresecultural aspect